Забезпечення зростання міжнародної конкурентоспроможності національного приладобудування - Duginets, Ganna; Kotlubai, Viacheslav (Dr. Viktor Koval, 2020)
Introduction. Mechanical engineering and instrument-making is one of the most science-intensive industries and the level of development of instrument-making directly depends on the main indicators of socio-economic development of the state. At the same time, in Ukraine this industry and its products lag behind the world level due to a number of objective reasons, which are of economic, political and technological nature. Lagging in technologies, lack of domestic innovations and high cost of new equipment make it necessary for enterprises to replace the main production assets, as well as to complete the final reorientation of the economic model of development. Aim and tasks. Study the state of instrument-making products of Ukraine, with subsequent identification of areas to improve its competitiveness. Results. The dynamics of indices of industrial production during 2015-2019 was analyzed and the share of instrument-making in industry from 2015 to 2019 was identified. PEST-analysis of domestic instrumentation was carried out to identify economic, political, social and technological factors affecting its competitiveness. The sufficient efficiency of instrument-making enterprises is justified taking into account methodological postulates of the theory of effective competition. Certain fluctuations can be explained firstly by the presence of crisis phenomena in the Ukrainian economy in 2014-2015. And secondly, the dynamics of indicators is closely related to the processes within the company. On the other hand, the analysis of the export structure indicates a decrease in the volume of high-tech products due to the lack of international competitiveness of the industry. Conclusions. It is proved that the development of instrument-making enterprises is cyclical. The main directions of increasing the competitiveness of domestic instrument-making enterprises and their products on world markets are proposed, namely: updating of the entire technological platform of instrument-making; launching production of new high-tech products that are more innovative and knowledge-intensive, development of international cooperation and cooperation, a course to develop the scientific environment in the field of instrumentation.